Sub-ppm electrical detection of hydrogen sulfide gas at room temperature based on printed copper acetate–gold nanoparticle composite films1. Issue 18 (5th March 2015) - Sarfraz, J.; Määttänen, A.; Törngren, B.; Pesonen, M.; Peltonen, J.; Ihalainen, P.
<x xml:space="preserve">Abstract</x> This paper presents the sub-ppm level electrical detection of H2S gas at room temperature using printed copper acetate–gold nanoparticle composite films either on (A) silver or (B) gold/AuNP electrodes.